ANALISIS WACANA KRITIS MODEL VAN DIJK DALAM PEMBERITAAN ATURAN PENGGUNAAN TOA MASJID DAN PERNYATAAN MENAG YAQUT MENGANALOGIKAN SUARA AZAN DENGAN GONGGONGAN ANJING DI MEDIA ONLINE TEMPO.COM - Pepi Supita; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This study focuses on the coverage of Minister of Religious Affairs Yakut's statement regarding the call to prayer (azan) compared to the sound of barking dogs currently happening in Indonesia, as published in several online media outlets, particularly Tempo.com. While there are numerous other online media sources producing news related to this issue, the researcher attempts to analyze these two specific online media outlets. The aim of this study is to describe the critical discourse analysis of the "Regulation on the Use of Mosque Loudspeakers and Minister Yakut's Statement Analogizing the Azan with Dog Barking" found in the news article titled "Yaqut Reported Regarding Azan and Dog Barking, Here's What the Ministry of Religious Affairs Says" published on Tempo.com. The theoretical framework employed for the analysis is Teun A. Van Dijk's Critical Discourse Analysis. The research methodology used in this study is descriptive qualitative. Based on the conducted analysis, it was found that the news article attempts to convey a message to readers regarding the pros and cons of the Minister's Regulation on the use of loudspeakers in mosques and the statement analogizing the Azan with dog barking. This is influenced by the social cognition of the news article's author and the social context in which the news article is produced. This is evident in the discourse structure of the news article, which conveys a message of religious tolerance amidst a diverse society with varying beliefs. Keywords: Critical Discourse Analysis, Ministerial Rules, social context.